A Clinical educator's experience using a virtual patient to teach communication and interpersonal skills - Banski, Frank; Beilby, Janet; Quail, Michelle; Allen, Peter; Brundage, S.; Spitalnick, J. (ASCILITE, 2018)
The purpose of this study was to explore one novice clinical educator’s experiences with training essential communication and interpersonal skills using a virtual patient. Over 3 weeks, the clinical educator (CE) delivered a series of half-day clinical placements to students using an educator-controlled virtual patient, depicting an older adult male with mild dementia. Students completed one 15-minute session interacting with the virtual patient in the virtual learning environment (VLE), followed by a group debrief/discussion session. Prior to, during and after delivering the clinical placements, the CE engaged in semi-structured interviews, where she was prompted to reflect on her pedagogic approach and practice. Thematic analysis revealed six themes underpinning the CE’s unique narrative: pedagogical control, validation of pedagogical practice, safety in the virtual learning environment, learning pedagogical practices, self-reflection, and adult education. The CE described how being immersed in the VLE allowed her to confidently deliver training. The findings have implications for the future training of CEs who will provide clinical education using VLEs in clinic settings.